THE FISCAL FEDERALISM AND THE GOOD ECONOMIC GOVERNANCE IN EUROPEAN UNION - Alina Ligia Dumitrescu (Global Economic Observer)
The research objectives aim to analyze the advantages and the disadvantages of the fiscal federalism, in order to identify the model of economic governance that will increase the quality and efficiency in public intervention. The fiscal federalism could have an important impact on the economic and political level in EU, but mostly in member states, in order to obtain a better administration and more responsible governance for the resources allocation, income distribution and fiscal consolidation. Fiscal federalism can bring to Romania advantages towards accessing more European funds and achieving budgetary discipline, and the last but not the least for stimulating economic growth.